2021
DOI: 10.1155/2021/8819780
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Thin-Layer Drying Kinetics of Marinated Beef during Infrared-Assisted Hot Air Processing of Biltong

Abstract: Biltong is a dried meat product that is widely consumed in South Africa. The marinated meat is traditionally dried under ambient winter conditions while commercial biltong producers use hot air driers. Hot air drying is time-consuming and energy-intensive. A combined infrared and hot air drying (IRHAD) is an alternative method of drying meat during biltong processing. The aim of this study was to establish the effect of the infrared (IR) power, the temperature, and velocity of the drying air on the drying kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Tezcan et al, 2021 studied the thin‐layer drying of dill leaves in continuous type IR dryer and reported the D eff values of 6.97 × 10 −9 , 6.84 × 10 −9 and 8.96 × 10 −9 m 2 /s for power intensities of 1,790, 1,970 and 2,070 W/m 2 , respectively. The effective moisture diffusivity values of 4.560 × 10 −10 to 13.7 × 10 −10 m 2 /s was reported by Muga, Marenya, and Workneh (2021) during a combined IR and hot air drying of biltong at IR power levels of 500, 750, and 1,000 W; drying air temperatures of 30, 35, and 40°C; and air velocity of 1.5 and 2.5 m/s. Taghinezhad et al (2021) observed the effective moisture diffusivity values of 1.007 × 10 −9 to 8.1110 −9 m 2 /s during drying of turnip slices in a hybrid convective‐IR dryer.…”
Section: Drying Kinetics Of Food Materials In Ir and Ir‐assisted Dryingsupporting
confidence: 58%
See 1 more Smart Citation
“…Tezcan et al, 2021 studied the thin‐layer drying of dill leaves in continuous type IR dryer and reported the D eff values of 6.97 × 10 −9 , 6.84 × 10 −9 and 8.96 × 10 −9 m 2 /s for power intensities of 1,790, 1,970 and 2,070 W/m 2 , respectively. The effective moisture diffusivity values of 4.560 × 10 −10 to 13.7 × 10 −10 m 2 /s was reported by Muga, Marenya, and Workneh (2021) during a combined IR and hot air drying of biltong at IR power levels of 500, 750, and 1,000 W; drying air temperatures of 30, 35, and 40°C; and air velocity of 1.5 and 2.5 m/s. Taghinezhad et al (2021) observed the effective moisture diffusivity values of 1.007 × 10 −9 to 8.1110 −9 m 2 /s during drying of turnip slices in a hybrid convective‐IR dryer.…”
Section: Drying Kinetics Of Food Materials In Ir and Ir‐assisted Dryingsupporting
confidence: 58%
“…Higher the value of E a higher is the sensitivity of D eff . E a values of food and agricultural products are ranged from 12 to 130 kJ/mol and Table5shows the activation energy values of various food materials Muga et al (2021). recorded the activation energy values ranged between 40.97 and 59.16 kJ/mol during a combined IR and hot air drying of biltong at IR power levels of 500, 750, and 1,000 W; drying air temperatures of 30, 35, and 40 C; and air velocity of 1.5 and 2.5 m/s.…”
mentioning
confidence: 99%
“…When it comes to dried meat products like biltong, the absence of a heat lethality phase raises doubts about whether or not the processing of biltong can effectively minimize the number of microbial pathogens available [28]. Despite the fact that commercial biltong manufacturers make use of hot air dryers, the meat that is traditionally marinated is often dried outside throughout the winter months [48]. In addition, drying with hot air demands a significant amount of both time and effort.…”
Section: Biltongmentioning
confidence: 99%
“…Of increasing interest is grilling, which is among such thermal processes that involve temperatures above 150 °C transferred by conduction, and through direct/radiant dry heat ( Schröder, 2003 ; Ježek et al, 2020 ). More so, the application of grilling of various types to meat products has been reported by several workers ( Farhadian et al, 2010 ; Kerth, Blair–Kerth & Jones, 2003 ; Khan et al, 2015 ; Muga, Marenya & Workneh, 2021 ; Gómez, Ibañez & Beriain, 2019 ; Vişan et al, 2021 ). Whereas Muga, Marenya & Workneh (2021) performed modeling thin-layer drying kinetics of marinated beef submitted to infrared-assisted hot air processing, and Gómez, Ibañez & Beriain (2019) investigated the physicochemical and sensory properties of sous vide meat and meat analog products marinated and cooked at different temperature-time combinations, Vişan et al (2021) studied the marination of Black Angus beef meat subjected to a grilling process.…”
Section: Introductionmentioning
confidence: 98%
“…More so, the application of grilling of various types to meat products has been reported by several workers ( Farhadian et al, 2010 ; Kerth, Blair–Kerth & Jones, 2003 ; Khan et al, 2015 ; Muga, Marenya & Workneh, 2021 ; Gómez, Ibañez & Beriain, 2019 ; Vişan et al, 2021 ). Whereas Muga, Marenya & Workneh (2021) performed modeling thin-layer drying kinetics of marinated beef submitted to infrared-assisted hot air processing, and Gómez, Ibañez & Beriain (2019) investigated the physicochemical and sensory properties of sous vide meat and meat analog products marinated and cooked at different temperature-time combinations, Vişan et al (2021) studied the marination of Black Angus beef meat subjected to a grilling process. Other cooking methods applied to beef meat, which paved way for examination and prediction of other quality attributes ( Kondjoyan et al, 2014 ; Onopiuk et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%